Trichocera (Metatrichocera) mackenziei Dahl 1967 ... - Petrašiūnas, Andrius; Podėnas, Sigitas (Zenodo, 2011)
Trichocera (Metatrichocera) mackenziei (Dahl, 1967) Metatrichocera mackenzie Dahl, 1967. Dahl, 1967a: 60. Trichocera (Metatrichocera) mackenziei (Dahl, 1967). Dahl & Alexander, 1976: 14. Illustrated by Dahl, 1967a: figs. 11–15, 57–60; Dahl, 1967b: figs. 12–14; Dahl & Krzemińska, 1997: figs. 34–35; Pratt, 1992: fig. 12; Pratt, 2003: fig. 12. Material examined. MONGOLIA: 1 male, Hovsgol Aimag, Khankh Soum, Noyon river bank, 8–15 August, 2005, Malaise trap, coll. O. Yadamsuren and S. Enkhtaivan, habitat: narrow valley with boggy forb-sedge meadow (Carex sp., Leymus chinensis, Potentillia sp.), vegetation coverage 70 percent, malaise trap at river edge; 1 female, Hovsgol Aimag, Ulaan Uul Soum, bogs and streams 800 m from Bagtag Gol (river), N50.81208 E99.33510, elevation 1590 m, 30.VI.2006, Selenge River Basin Insect Survey Project # 06062904. The species was known from Northern Canada (Dahl, 1967), Northern Sweden and Finland (Dahl & Alexan- der, 1976) and Russian Kola Peninsula (Lantsov & ... : Published as part of Petrašiūnas, Andrius & Podėnas, Sigitas, 2011, Notes on winter flies Trichoceridae (Diptera) of Mongolia with description of new species, pp. 61-68 in Zootaxa 3031 on pages 62-63, DOI: 10.5281/zenodo.278712 ...